2014
DOI: 10.5897/ijgmb2013.0083
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in conserving and utilizing plant genetic resources (PGR)

Abstract: The problems of food and income security are of global significance and are further compounded by precedential increase in world population resulting in overexploitation of natural resources and by extension plant genetic diversity. Plant genetic resources (PGR) refer to the heritable materials contained within and among plant species of present and potential value. In the recent past, genetic diversity found in landrace, weedy and wild cultivars have been reported to savage animal and plant population disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(16 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In this context, knowledge on all aspects of genetic diversity viz., factors affecting genetic diversity, different methods of diversity analysis, their measurement and the softwares for carrying statistical analysis becomes imperative in order to utilize them prudently. Many reviews have been written focusing on vital issues like changes in genetic diversity under plant breeding [1], genetic vulnerability of modern crop cultivars [2], conservation and utilization of genetic resources [3,4] assessment of genetic diversity using molecular markers [5] and measurement of genetic diversity using statistical tools [6][7][8]. In the present review, an attempt is being made for comprehensive compilation of overall concepts in the area of genetic diversity, which could be of immense significance for extending knowledge and meaningful research.…”
mentioning
confidence: 99%
“…In this context, knowledge on all aspects of genetic diversity viz., factors affecting genetic diversity, different methods of diversity analysis, their measurement and the softwares for carrying statistical analysis becomes imperative in order to utilize them prudently. Many reviews have been written focusing on vital issues like changes in genetic diversity under plant breeding [1], genetic vulnerability of modern crop cultivars [2], conservation and utilization of genetic resources [3,4] assessment of genetic diversity using molecular markers [5] and measurement of genetic diversity using statistical tools [6][7][8]. In the present review, an attempt is being made for comprehensive compilation of overall concepts in the area of genetic diversity, which could be of immense significance for extending knowledge and meaningful research.…”
mentioning
confidence: 99%
“…Moreover, it will be the representative voice for Nigeria vegetable interests and monitor activities such as the recently AVRDC funded onion storage facility in Sokoto state, Northwestern Nigeria. Moreover, this indigenous centre will contribute to understanding the diversity of vegetable and help prevent threats to their sustainable utilisation and conservation [2,96,97].…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…However, domestication and selection of maize are said to cause reduced genetic diversity in the maize genome as compared with its progenitor population (Pineda-Hidalgo et al, 2013). The reduction in the genetic diversity of crops represents an increase in vulnerability to new pests and diseases (De Jaramillo, 2009;Ogwu et al, 2014). It has been reported that about 80% of African farmers grow only landraces since they are able to reuse the seeds in many seasons while on the other hand only 20% grow improved varieties together with landraces (Anjichi et al, 2005).…”
Section: Importance Of Landracesmentioning
confidence: 99%